2008
DOI: 10.1080/00288230809510438
|View full text |Cite
|
Sign up to set email alerts
|

Pasture responses to phosphorus and nitrogen fertilisers on east coast hill country: 2. Clover and grass production from easy slopes

Abstract: From 2000 to 2002 a trial series was established on seven farms from Wairoa (northern Hawke's Bay) to Moeraki (North Otago), with contrasting amounts of spring-summer rainfall, to evaluate the pattern of pasture responses to a range of rates of nitrogen (N) fertiliser and a range of soil phosphorus (P) levels. Small plots excluded from grazing were established on flat to gently sloping land containing pastures that had been established for many years. This paper describes the clover and grass component product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The response by pasture on steep slopes to increase in soil P was mainly limited to early spring, whereas on easy slopes most sites also responded in late spring-autumn (Gillingham et al 2008). The clover component of the pasture was responsive to increase in soil P test in both seasons on both land classes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The response by pasture on steep slopes to increase in soil P was mainly limited to early spring, whereas on easy slopes most sites also responded in late spring-autumn (Gillingham et al 2008). The clover component of the pasture was responsive to increase in soil P test in both seasons on both land classes.…”
Section: Discussionmentioning
confidence: 87%
“…This was used to derive an estimate of clover production and, by difference, grass production. The limitations of this approach were discussed by Gillingham et al (2008). The pasture was then trimmed to approximately 900 kg Dm ha -1 residual pasture and clippings removed.…”
Section: Measurementsmentioning
confidence: 99%
“…At grass grub densities similar to those found in the Allophanic high-intensity pasture, productivity of ryegrass clover mixtures can be reduced by up to 50% (East et al 1982). Indeed, their feeding behaviour was apparent with a decline in root mass and legume contribution to the pasture (Table 2), as Gillingham et al (2008) observed an increase in legumes with increased phosphate application. Competition with other herbivorous fauna (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This Olsen P concentration is just below the average of 20 mg/ml derived for sedimentary soils (Morton & Roberts 2010) and less than the critical level for sedimentary soils of 26Á32 mg/ml reported by Edmeades et al (2006), but falls within the scatter of field trial results presented in their paper. Furthermore, work by Sinclair et al (1997) and Gillingham et al (2007Gillingham et al ( , 2008 showed that there is little advantage in sheep pastures of Olsen P concentrations greater than 20 mg/ml. Nguyen et al (1989) showed that SSP application resulted in high-producing ryegrass and clover pastures in the initial years, and that cessation of fertiliser on some plots in 1958 resulted in an increase in weeds and poor producing/lower fertility grasses and a decrease in clover content.…”
Section: P Response Curvesmentioning
confidence: 99%
“…There were several occasions over the duration of the trial when this irrigation scheduling system was not applied, for a variety of reasons. These occurred in 1954 and 1984 (Rickard & McBride 1987) and latterly in 2007and 2008. Between 1952and 1958, the trial evaluated the effects of five different SSP treatments (Rickard & Moss 2012) initially applied in autumn, but in later years applied in late winter (Rickard and McBride 1987;Nguyen et al 1989).…”
Section: Trial Sitementioning
confidence: 99%